A STUDY OF PATRON-CLIENT RELATIONSHIP BETWEEN FISHERMAN AND SUPPLIER IN KEMA - Humbas, Jeniffer G.; Massie, James D.D.; Wangke, Shinta J.C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Â A patron-client relationship is an ongoing relationship, often contractual, in which a powerful or influential person provides rewards and services to a lesser and weaker person in return for loyalty and support, and may also include a reciprocal exchange of some services. This study aims to better understand the benefits for each business actor involved in patron-client relationships. The researcher conducted this research through qualitative method to understand the role of patron-client relationship. The population studied in this study are suppliers who partner with fishing companies who are also owners of fishing vessels, and fishermen who supply fish to suppliers.The researcher concludes that the relationship between suppliers and fishermen has a good and positive impact because all informants benefit during this collaboration, where suppliers get fish to produce and fishermen get profits to fulfill their daily needs. It is also possible for future studies to include samples from other populations for more informative findings and to enlarge the sample size and conduct different tests on the benefits that suppliers and fishermen derive from engaging in patron-client relationships.Â Keyword:patron-client, relationship, partnership, fisheries resources management